Efektivitas Logoterapi Medical Ministry terhadap Kebermaknaan Hidup pada Warga Binaan dengan HIV/AIDS - Widiyastuty, Riesma; Wangi, Eneng Nurlaili; Fahmi, Irfan (Jurnal Psikologi Perseptual, 2023)
This research aims to determine the effectiveness of logotherapy medical ministry on the level of meaning in life among five inmates with HIV/AIDS. Participants are guided to understand the inevitable tragic experiences through the ability to take a stance and undergo a self-transcendence process, which is a distinctive feature of medical ministry compared to other logotherapy techniques. It focuses on understanding and evaluating the "past and present" and then connecting it with something meaningful "outside oneself and in the future." This approach combines spiritual and psychological elements to address existential problems and provide support. The research design was selected based on the consideration of a limited number of participants, employing a one-group pretest-posttest design. The Meaning in Life Questionnaire (MLQ) is a validated instrument assessing the presence of meaning and the search for meaning in life. MLQ by Michael F. Steger and Patricia Frazie (Indonesian version), was used as the measurement tool for assessing the level of meaning in life has a reliability of 0.861 and validity ranging from 0.328 to 0.841. The N-Gain result of 57.75% indicates a significant increase in the participants' meaning in life. Penelitian ini bertujuan untuk mengetahui evektivitas logoterapi medical ministry terhadap tingkat kebermaknaan hidup pada lima warga binaan dengan HIV/AIDS. Partisipan penelitian dibimbing untuk memahami pengalaman tragis yang tak terhindarkan dengan kemampuan mengambil sikap dan proses transendensi diri yang menjadi ciri khas teknik medical ministry dibandingkan teknik logoterapi lainnya, yaitu untuk memahami dan mengevaluasi keadaan “di masa lalu dan sekarang” kemudian menghubungkannya dengan sesuatu yang bermakna “di luar diri sendiri dan di “masa depan”, yang menggabungkan pendekatan spiritual dan psikologis untuk mengatasi masalah eksistensial dan memberikan dukungan. Pemilihan desain penelitian berdasarkan pertimbangan jumlah partisipan yang terbatas, sehingga menggunakan one-group pretest-posttest design. The Meaning in Life Questionnaire (MLQ) diberikan untuk mengukur perubahan tingkat makna hidup partisipan sebelum dan sesudah intervensi. MLQ adalah instrumen tervalidasi yang menilai presence of meaning dan search for meaning in life. Meaning in Life Questionnaire (MLQ) dari Michael F. Steger dan Patricia Frazie versi bahasa Indonesia digunakan sebagai alat ukur pre-test dan post-test untuk mengukur tingkat kebermaknaan hidup. Alat ukur ini memiliki reliabilitas 0.861 dan validitas 0.328-0.841. Hasil N-Gain 57.75% menunjukan peningkatan kebermaknaan hidup yang cukup signifikan